2011
DOI: 10.1038/npp.2010.235
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Response Inhibition and Cigarette Smoking in Late Adolescence

Abstract: Smoking is usually initiated in adolescence, and is the leading preventable cause of death in the United States. Little is known, however, about the links between smoking and neurobiological function in adolescent smokers. This study aimed to probe prefrontal cortical function in late adolescent smokers, using a response inhibition task, and to assess possible relationships between inhibition-related brain activity, clinical features of smoking behavior, and exposure to cigarette smoking. Participants in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 60 publications
(81 reference statements)
2
70
1
1
Order By: Relevance
“…Studies in adolescent animals also show that exposure to nicotine results in suppressed neural activity and persistent desensitization of cholinergic responses (Slotkin, 2008). Furthermore, prior studies by our research group using functional magnetic resonance imaging to study a subset of the participants in the present study have shown that the Heaviness of Smoking Index is related to brain activation during response inhibition and risky decision making in emergent adults (Galvan et al, 2011;Galvan et al, 2013), suggesting that alterations in brain function related to smoking may have a meaningful impact on behavior. Together, these studies begin to reveal a holistic picture of the effects of smoking on the developing brain, and future work to integrate these findings may lead to a better understanding of the neural mechanisms that support addiction.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies in adolescent animals also show that exposure to nicotine results in suppressed neural activity and persistent desensitization of cholinergic responses (Slotkin, 2008). Furthermore, prior studies by our research group using functional magnetic resonance imaging to study a subset of the participants in the present study have shown that the Heaviness of Smoking Index is related to brain activation during response inhibition and risky decision making in emergent adults (Galvan et al, 2011;Galvan et al, 2013), suggesting that alterations in brain function related to smoking may have a meaningful impact on behavior. Together, these studies begin to reveal a holistic picture of the effects of smoking on the developing brain, and future work to integrate these findings may lead to a better understanding of the neural mechanisms that support addiction.…”
Section: Discussionmentioning
confidence: 80%
“…As described in a previous report (Galvan et al, 2011), participants were recruited through online and print advertisements. After receiving a detailed explanation of the study (approved by the UCLA Institutional Review Board), participants X18 years of age gave written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…The findings of a study involving adolescents with nicotine dependence who abstained from smoking for 30-1050 minutes before scanning support this hypothesis. 64 While adolescents with nicotine dependence and controls had similar accuracy rates and brain activation, the study found that severity of smoking within those with nicotine dependence was associated with lower activation in regions critically involved in inhibitory control (i.e., ACC, SMA, left IFG, left orbitofrontal cortex [OFC], bilateral MFG and right SFG).…”
Section: Inhibitory Control In Individuals With Nicotine Dependencementioning
confidence: 98%
“…Already at early stages of smoking, the degree of smoking behavior and dependence, assessed by the Heaviness of Smoking Index (Robinson and Kolb, 1997), was negatively associated with the response in the prefrontal cortex during response inhibition (Borland et al, 2010). Furthermore, the response in the prefrontal cortex was significantly lower in adolescent smokers compared with non-smokers during response inhibition (Galván et al, 2011), and a working memory task in smoking abstinent adolescents (Musso et al, 2007). In addition, clinical features of smoking behaviors-cigarette dependence and number of cigarettes smoked per day-were negatively related to cortical activity during response inhibition (Galván et al, 2011).…”
Section: Introductionmentioning
confidence: 96%